THE PHENOMENA OF BEHAVIOR HANDLING IN COFFEE SHOPS AS A PUBLIC SPACE: STUDY ON CONSUMERS OF DREAM COFFE KOPI STORES In BLITAR CITY - NOVI CATUR MUSPITA; AINUN NAJIB (Universitas Islam Balitar, 2021)
Along with the changing times and social changes in various fields, people's behavior is always dynamic in order to meet the needs of life. Including the behavior in drinking coffee, nowadays, there have been many dynamic shifts influenced by western culture through the latest information and developments, this is evident from the start of the rise of coffee shops with various nuances: gelato, cafes, shops, and lesehan, as well as traditional coffee shops. For this reason, researchers are interested in researching with the aim of: (1) To determine the phenomenon of hanging out at a coffee shop as a public space: Studies on Consumers at Dream Caffe Coffee Shops, Blitar City, (2) To determine the meaning of hanging out at a coffee shop as a public space: Phenomenology Study of Consumers at Dream Caffe Coffee Shop, Blitar City. This study uses a qualitative method because it is to dissect the phenomenon and meaning of hanging out in a coffee shop in depth. The results showed: (1) The phenomenon of hanging out at a coffee shop as a public space: Studies on Consumers at Dream Coffe Coffee Shops in Blitar City: Characteristics of consumers of Dream Coffe coffee shops are dominated by young people ranging from junior high school to high school students, students, and general public with an average age between 15 - 40 years, (2) The meaning of hanging out at the Warung: getting a relaxed and calm atmosphere, to find inspiration and ideas, to chat with friends, to join Zoom Meetings and read social books and Politics, discussion and discussing business,